Cracking the code of plant central phosphate signaling. (March 2023) - Jia, Xianqing; Wang, Long; Nussaume, Laurent; Yi, Keke
Abstract: Phosphate (Pi) is involved in numerous metabolic processes and plays a vital role in plant growth. Green plants have evolved intricate molecular bases of Pi signaling to maintain cellular Pi homeostasis. Here, we summarize recent advances in the molecular and structural bases of central Pi signaling and discuss pending questions.